Stinky Cecil in Terrarium terror! - Braddock, Paige (Braddock, Paige. Stinky Cecil, 2016)
Cecil and his amphibian pals are taking a well-deserved break after saving their pond from freeway construction when a third-grade science class shows up for a field trip. The kids nab Cecil for their classroom terrarium! At first Cecil is terrified, but he quickly gets used to being a class pet. That is, until Nesbit the chameleon shows up. Nesbit wants to be just like Cecil, so he matches his colors and follows him all around the terrarium. He's driving Cecil crazy! Meanwhile, Cecil's pals back at the pond are planning a rescue mission using Jeff the hamster's radio controlled helicopter. But what will they do about Nesbit?